Modeling the Rice Self-Sufficiency in the Philippines - Rubin, Benjamin D.; Mayo, Francis; Maglasang, Renan S. (Science & Technology Asia, 2024)
We study the interactions between the production and consumption of rice along with the several factors which involve a number of changes to the production and consumption through system dynamics modeling. We focus on three scenarios on the system dynamics model, which entails the possible effect on rice self-sufficiency and import dependency ratio by simulating the realistic values on rice production and rice consumption based on the PSA data. Historical data from 1995 was utilized and analyzed to build the model to have meaningful information regarding how the system behaves with the various factors in the system. After the model has been validated, several scenarios are simulated and their impact analyzed on the different sustainability dimensions, specifically the Philippines' Agricultural Indicator System. Results showed that production and consumption interventions are crucial to improving the Philippines' self-sufficiency and import-dependency ratio. Keywords: Rice; Self Sufficiency; System dynamics modelling